Variability of essential oil constituents of Ocimum africanum - Pisutthanan, Nisit; Pisutthanan, Sirintorn (Asian Health, Science and Technology Reports, 2009)
Aerial parts of Ocimum africanum Lour. (Lamiaceae) collecting from three different locations of Thailand, including the northern, northeastern and southern parts, were evaluated for their volatile constituents. Their essential oils were obtained by hydrodistillation method. The chemical composition of the essential oil was analyzed by means of gas chromatography mass spectrometry using standard nalkane mixtures as internal standards. All samples of Hoary basil essential oil were characterized by a high percentage of monotepenes, represented especially by neral (range from 21.1% to 36.8%) and geranial (range from 15.6% to 33.4%). The major components of essential oil from the northern part were neral (36.8%), geranial (33.4%), (E)caryophyllene (3.5%), and linalool (3.1%), whereas the oil from the northeastern part comprised neral (21.1%), geranial (15.6%), linalool (8.9%), (E)caryophyllene (7.7%), germacrene D (5.5%), and alphahumulene (3.5%). Finally, the essential oil from the southern part contained neral (24.4%), geranial (22.8%), methyl chavicol (9.4%), linalool (5.6%), and (E)caryophyllene (5.5%). Therefore, all three essential oils of O. africanum collected from different locations of Thailand could be considered as the same neral/gernial chemotype. According to the literatures, eight different chemotypes were recorded for the essential oil of O. africanum and the result of this study revealed that high neral/geranial contents in the essential oil of this species could be identified as a novel chemotype.